Effects of Feeding Milk Replacer Ad Libitum or in Restricted Amounts for the First Five Weeks of Life on the Growth, Metabolic Adaptation, and Immune Status of Newborn Calves - Schäff, Christine T. (PLoS One, 2016)
The pre-weaning period is critical for calf health and growth, and intensive milk feeding programs may assist postnatal development by improving body growth and organ maturation. The aim of the present work was to study the effects of ad libitum milk replacer (MR) feeding on the growth, metabolic adaptation, health, and immune status of newborn calves. Twenty-eight newborn Holstein and Holstein x Charolais crossbred calves were fed ad libitum (ADLIB) or in restricted amounts (6 liters per day; RES) during the first five weeks of life. The MR intake in the ADLIB treatment was gradually reduced at weeks 6 and 7, and all calves then received 6 liters of MR per day until day 60. Blood samples were collected to measure the plasma concentrations of metabolites, insulin, insulin-like growth factor (IGF)-I and IGF binding proteins (IGFBP), immunoglobulins, and acute phase proteins. The expression of mRNA associated with both the somatotropic axis and gluconeogenic enzymes was measured in the liver on day 60. Intensive feeding improved MR intake and growth in ADLIB without influencing concentrate intake. Carcass weight, perirenal fat, and muscle mass were greater in ADLIB. Plasma concentrations of glucose, triglycerides, insulin, and IGF-I were greater, whereas plasma concentrations of β-hydroxybutyrate, total protein, albumin, urea, IGFBP-2 and -4, and fibrinogen were lower at distinct time points in ADLIB. The hepatic mRNA expression of cytosolic phosphoenolpyruvate carboxykinase was greater in ADLIB. Most metabolic and endocrine differences occurred during the MR feeding period, but a slightly greater concentrate intake was associated with increased plasma IGF-I and insulin at the end of the study. The immune and health status of the calves were not affected by MR feeding. However, increased plasma fibrinogen in the RES group suggested differences in the acute phase response.